Astrocytic Calcium Dynamics Along the Pain Pathway - Cho, Jeiwon; Huh, Yeowool (Frontiers in Cellular Neuroscience, 2020)
Astrocytes, once thought to be passive cells merely filling the space between neurons in the nervous system, are receiving attention as active modulators of the brain and spinal cord physiology by providing nutrients, maintaining homeostasis, and modulating synaptic transmission. Accumulating evidence indicates that astrocytes are critically involved in chronic pain regulation. Injury induces astrocytes to become reactive, and recent studies suggest that reactive astrocytes can either have neuroprotective or neurodegenerative effects. While the exact mechanisms underlying the transition from resting astrocytes to reactive astrocytes remain unknown, astrocytic calcium increase, coordinated by inflammatory molecules, has been suggested to trigger this transition. In this review, we will discuss the roles of astrocytic calcium, channels contributing to calcium dynamics in astrocytes, astrocyte activations along the pain pathway, and possible relationships between astrocytic calcium dynamics and chronic pain.